The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.21638/11701/spbu08.2016.302
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Strategic Human Resource Management trough the Lens of High Performance Work System

Abstract: А. К. Бордунос, С. В. Кошелева ЭВОЛЮЦИЯ СТРАТЕГИЧЕСКОГО ПОДХОДА К УПРАВЛЕНИЮ ЧЕЛОВЕЧЕСКИМИ РЕСУРСАМИ С ПОЗИЦИЙ СИСТЕМ ОРГАНИЗАЦИИ ТРУДА Санкт-Петербургский государственный университет, Российская Федерация, 199034, Санкт-Петербург, Университетская наб., 7-9 В статье представлен критический обзор эволюции стратегического подхода к управлению человеческими ресурсами, основу которого в разное время составляли высокорезультативные системы организации труда (СОТ). Решая проблему неустойчивости результатов СОТ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Work systems as frames of reference for HR disclosure РЖМ 17 (3): 309-336 2019ingly routinized it as a standardized internal practice. Institualization of the GRI report ing inspired shift to the sustainable develop ment, associated with the highcom mit ment work system [Bordunos, Kosheleva, 2016].…”
Section: Preference Of Work Systems By Banks In Russiamentioning
confidence: 99%
See 1 more Smart Citation
“…Work systems as frames of reference for HR disclosure РЖМ 17 (3): 309-336 2019ingly routinized it as a standardized internal practice. Institualization of the GRI report ing inspired shift to the sustainable develop ment, associated with the highcom mit ment work system [Bordunos, Kosheleva, 2016].…”
Section: Preference Of Work Systems By Banks In Russiamentioning
confidence: 99%
“…In such situations, the role of banks is reflected in their posi tion in interorganizational networks, in tensified by affiliation with particular busi ness groups, invitation to boards of directors or on management positions representatives of important businesspartners, govern ments, and shareholders [Okhmatovskiy, 2005]. These facts highlight the importance of social capital, suitable for highin volve ment work system [Bordunos, Kosheleva, 2016]. Furthermore, the growing role of tech nology, adjustments in government regula tions, industry consolidation, financial in novation and securitization [Wilson et al, 2010] intensify favoring dynamic capabili ties concept that requires highin volve ment work system.…”
Section: Preference Of Work Systems By Banks In Russiamentioning
confidence: 99%
“…Surprisingly, the review [21] revealed that the alternative fit requirements do not contradict each other, allowing additivity. Challenges cause institutional sophistication (saturation) and institutional voids (gaps).…”
Section: Latent Referent Standards 21 Methodological Concernsmentioning
confidence: 98%
“…Empirically, such approach is even more complicated due to uncertain effects between the mixed patterns [6]. In our previous research [21] we were interested if it is possible to operationalize the concept in a way to avoid a need in a segregation of HRMS into a bunch of patterns. We expected effect similar to the additive RGB color model [22], when latent additive primary lights of certain intensity, been projected jointly on the black background, can reproduce high variety of other colors.…”
Section: Latent Referent Standards 21 Methodological Concernsmentioning
confidence: 99%
“…При этом в отечественных научных журналах эти термины употребляются крайне редко, также как и их русскоязычный аналог -ВПРМ, появившийся на государственном уровне уже достаточно давно как некий целевой ориентир. В практике управления организациями реализация обозначаемых данными терминами подходов идет не совсем параллельными путями, примерно так же, как произошло с предложенной в 1999 г. Международной организацией труда концепцией "достойного труда": на уровне макроэкономики и соответствующих социальных процессов исследователи и практики заботятся о минимизации безработицы, равных трудовых правах всех социальных групп и "защищенном уровне оплаты труда" 2 , 3 . При этом на уровне отдельных компаний возможности повышения заработной платы зависят от степени эффективности и конкурентоспособности этих компаний, однако задача создания "достойных рабочих мест", способных повышать эту эффективность (помимо необходимых, но дополнительных затрат, на которые не все компании способны), испытывает трудности в реализации, в том числе и из-за противоречивых трактовок употребляющихся в этой сфере терминов.…”
Section: экономическая социология и менеджментunclassified